Improving Students' Multiplication Learning Outcomes Through the Implementation of PBL Model with P4 Basket Media - Nimas Wina Lestari; Eva Nurul Malahayati; Sripit Widiastuti (Program Studi PGSD Universitas Madako Tolitoli, 2024)
Mathematics learning at the elementary school level has a crucial role in students' cognitive development. Although it is often perceived as a boring and difficult material, especially in understanding the concept of multiplication, this study aims to evaluate the effectiveness of the Problem Based Learning model (PBL) combined with the P4 basket media in improving students' problem-solving skills, understanding of mathematical concepts, and cognitive thinking skills. This study uses a quasi-experimental design by involving grade III students at SDN Kanigoro 03 Blitar Regency as a control and experimental group. The purposive sampling method was applied to select 26 students from class IIIA as the control group and 26 students from class IIIB as the experimental group. The instruments used in this study include observation sheets to monitor the learning process and cognitive ability tests consisting of 25 questions, consisting of 15 multiple-choice questions and 10 short-fill questions. The results show that the application of the PBL model supported by the P4 basket media can improve students' learning outcomes in multiplication materials, improve their understanding of mathematical concepts, and improve analytical thinking skills. These findings indicate that PBL can be an effective approach in teaching mathematics at the primary school level.